FESTIVAL ATTRACTION SIAK SRI INDRAPURA DISTRICT - Iriani, Ade Mustika; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study aims to determine the praise Festival activities and to find out what are the attractions recite Festival in Siak Sri Indrapura. This study used qualitative methods, the nature of this research is descriptive research which describes in detail in accordance with the existing situation in the region Siak recite Festival on Festival Travel Attractions recite the Siak Sri Indrapura. The informant in this study is the Head of Tourism Promotion Siak, Head of Arts and Culture Tourism Management, Implementation Committee and some praise Festival City Community Leaders Siak Sri Indrapura who became a representative of the public perception of the Festival of praise as well as some tourists who aim to know more in how big attractions in the Festival recite in Siak Sri Indrapura. While data collection techniques in this research using questionnaires, interviews, observation and study of literature Based on the research that has been done, while the main attraction at the Festival praise is their uniqueness, beauty and value contained in various kinds of performances are presented, each in this stage has been getting a good response from the tourists who come to town Siak Sri Indrapura Siak praise for the Festival, it is because in this stage many tourists can find various kinds of arts and culture in the city of Malay Siak Sri Indrapura of each sub-district in the city of Siak Sri Indrapura which amounted to 14 districts, which all have a wide range of arts culture and customs are different. Keywords: Attraction, Festival recite, Siak District